Understanding China's Defensive-Moderate Approach to International Relations - Yakti, Probo Darono; Susanto, Siti Rokhmawati (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2025)
This article reinterprets Chinese foreign policy through the lens of strategic culture by advancing the concept of a defensive-moderate approach, defined as a deliberate blend of assertive defense and restrained diplomacy. While conventional analyses often rely on frameworks such as defensive realism or economic interdependence, this article emphasizes the formative role of Confucian values, including harmony, hierarchical order, and moral governance, in shaping China’s external behavior. Drawing on original research from a doctoral dissertation examining China’s interactions with the United States and India, this article explains how these values are internalized by elites, institutionalized in policy discourse, and manifested in practices such as preference for multilateralism, non-intervention, and calibrated responses to conflict. Through empirical illustrations from the Belt and Road Initiative, the Shanghai Cooperation Organization, and border management strategies, this article argues that China’s foreign policy is not merely reactive or materially driven but reflects a culturally informed strategic posture. This perspective challenges rationalist models of state behavior and offers a more nuanced understanding of China’s role in global affairs by highlighting the importance of socially constructed norms in foreign policy decision-making. Keywords: Strategic Culture, China, Confucianism, Foreign Policy, Defensive-Moderate Artikel ini menafsirkan ulang kebijakan luar negeri Tiongkok melalui lensa budaya strategis dengan mengajukan konsep pendekatan defensif-moderat, yang didefinisikan sebagai perpaduan yang cermat antara pertahanan asertif dan diplomasi tertahan. Sementara analisis konvensional sering mengandalkan kerangka seperti realisme defensif atau ketergantungan ekonomi, artikel ini menekankan peran nilai-nilai Konfusianisme seperti harmoni, tatanan hierarkis, dan pemerintahan bermoral dalam membentuk perilaku eksternal Tiongkok. Berdasarkan riset orisinal dari disertasi doktoral yang mengkaji hubungan Tiongkok dengan Amerika Serikat dan India, artikel ini menjelaskan bagaimana nilai-nilai tersebut diinternalisasi oleh para elite, dilembagakan dalam wacana kebijakan, dan diwujudkan dalam praktik seperti preferensi terhadap multilateralisme, non-intervensi, serta respons yang terukur terhadap konflik. Melalui contoh empiris dari Belt and Road Initiative, Organisasi Kerja Sama Shanghai, dan strategi pengelolaan perbatasan, artikel ini berargumen bahwa kebijakan luar negeri Tiongkok tidak sematamata bersifat reaktif atau didorong oleh kepentingan material, melainkan mencerminkan postur strategis yang didasarkan pada budaya. Perspektif ini menantang model-model rasionalis tentang perilaku negara dan menawarkan pemahaman yang lebih bernuansa mengenai peran Tiongkok dalam politik global dengan menyoroti pentingnya norma-norma sosial yang dikonstruksi dalam pengambilan keputusan kebijakan luar negeri. K Kata-kata Kunci: Strategic Culture, Tiongkok, Konfusianisme, Kebijakan Luar Negeri, Defensif-Moderat